Effects of Sulpiride on True and False Memories of Thematically Related Pictures and Associated Words in Healthy Volunteers - Guarnieri, Regina V.; Ribeiro, Rafaela L.; de Souza, Altay A. Lino; Galduróz, José Carlos F.; Covolan, Luciene; Bueno, Orlando F. A. (Frontiers in Psychiatry, 2016)
Episodic memory, working memory, emotional memory and attention are subject to dopaminergic modulation. However, the potential role of dopamine on the generation of false memories is unknown. This study defined the role of the dopamine D2 receptor on true and false memories. Twenty-four young, healthy volunteers ingested a single dose of placebo or 400 mg oral sulpiride, a dopamine D2-receptor antagonist, just before starting the recognition memory task in a randomized, double-blind, placebo-controlled trial. The sulpiride group made more false recognitions during visual and verbal processing than the placebo group although both groups had the same indices of true memory. These findings demonstrate that dopamine blockade in healthy volunteers can specifically increase the rate of false recognitions.